Peningkatan Pemahaman Dasar Jaringan Komputer bagi Siswa DKV melalui Sosialisasi Interaktif - Delia Anggraeni; Riska Suhela; Andhita Octaviana; Asharifa Sekar Kedasih (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
This community outreach program was initiated to foster foundational knowledge of computer networking among students in the Visual Communication Design (VCD) department at SMK Diponegoro 3 Kedungbanteng. Key topics included basic networking concepts, types and topologies of networks, hardware components, and their significance in creative fields. The implementation involved interactive learning through lectures, hardware demonstrations, and open discussions. A total of 46 students engaged in the sessions. The outcomes indicated increased engagement and awareness of interdisciplinary digital literacy, emphasizing the value of basic technology comprehension in collaborative design workflows.